Weed Management in Sesamum (Sesamum indicum L.) Grown under Coastal Region of Maharashtra - MANE, S V; KANADE, V M; SHENDAGE, G B; SARAWALE, P P; SHETYE, V N (Journal of the Indian Society of Coastal Agricultural Research, 2017)
An experiment was conducted to study the effect of mechanical and chemical weed control measures on growth and yield of sesamum during Rabi 2014 at Agronomy Farm, College of Agriculture, Dapoli. The experiment was laid out in randomized block design with ten treatments and three replications. The treatments mainly comprised of Pre Emergence application of (PE) Pendimethalin @ 0.75 kg a.i. ha-1 (T1), Pendimethalin (PE) @ 0.75 kg a.i. ha-1 + one hand weeding (HW) at 15 days after sowing (DAS) (T2), Pendimethalin (PE) @ 0.75 kg a.i. ha-1 + one HW at 30 DAS (T3), Pendimethalin (PE) @ 0.75 kg a.i. ha-1 + one HW at 45 DAS (T4), Post Emergence application of (POE) Quizalfop-ethyl 0.05 kg a.i. ha-1 (T5), Quizalfop-ethyl (POE) 0.05 kg a.i. ha-1 + one HW at 45 DAS (T6), HW at 30 DAS (T7), HW and hoeing at 45 DAS (T8), Weed free check (T9) and Weedy check (T10). Results revealed that, treatment weed free check produced significantly higher growth and yield attributes followed by treatment Pendimethalin (PE) @ 0.75 kg a.i. ha-1 + one HW at 30 DAS as compared to rest of the treatments under study